Testing the Dynamics of Flight for the Products of Explosion for a Warhead with a Weight of 250 kg - Andrzej M. FARYŃSKI; Andrzej DŁUGOŁĘCKI; Jarosław DĘBIŃSKI; Rafał KOŃKA; Tomasz KWAŚNIAK; Łukasz SŁONKIEWICZ; Zbigniew ZIÓŁKOWSKI (Problemy Mechatroniki)
This study presents the results of the testing of the explosion process of a warhead with a weight of 250 kg, filled with 87 kg of TNT with 20% of aluminium dust, in two configurations: with horizontal and vertical alignment of the warheads longitudinal axis, and with the centre of length of the warhead body located at a height of approx. 1 m above the ground. Four warheads were detonated in each configuration. The horizontal configuration allowed the collection of some amount of the fragments from the ground, with sizes and spatial distribution of the fragments corresponding to the location on the body from which they came, with the largest fragments from the central part of the shell measuring approximately 9 30 280 mm. For the vertical configuration, the warheads nose was pointed downwards, with an up-down excitation. In both configurations, the explosion process was recorded from a distance of 300 m using a PHANTOM fast camera with a time resolution (frame interval) of 55 s to 133 s: for the horizontal configuration along the bodys longitudinal axis, for the vertical configuration perpendicular to this axis. In the vertical configuration, the bodys expansion process was recorded using short-circuit sensors spaced every 5 mm along the flight radius. The sensors sent short-circuit signals to the time meter, whereas the first sensor was installed at a distance of approx. 1 mm from the body surface and was used to initiate the processes of time counting and recording the overpressure diagrams over time at the front of the explosion/shock (FU) wave. The recorded expansion velocity was approx. 1300 m/s, with the shell radius increasing by 20 mm. Overpressure at the front of the FU was measured by PCB pencil-tip piezoelectric sensors (CzP). Every sensor had two active surfaces arranged in tandem at a distance of 100 mm, which made it possible to determine the local FU velocity. Signals from CzP were recorded every 200 ns using a DEWETRON recorder with software allowing their initial and further processing. Three sensors were spaced 8 m from each other, whereas the first was located 8 m to 10 m from the warheads longitudinal axis. Under a row of the sensors a thick-wall steel pipe was placed to protect the sensors from destruction by the fragments. The determined local FU velocities varied from approx. (590 m/s to 740 m/s) at a distance of approx. 8 m from the epicentre up to approx. 370 m/s at a distance of approx. 26 m from the epicentre; the overpressure measured values varied from approx. (230 kPa to 550 kPa) at a distance of approx. 8 m to approx. 22 kPa at a distance of approx. 26 m from the epicentre; satisfying conformance of the velocity and pressure values under the flat FU model was found. The FU trajectory was also taken from the video recording the velocities measured varied from approx. 2,650 m/s at a distance of 0.3 m to approx. 670 m/s at a distance of 6 m from the epicentre, which corresponds to the CzP data. The fragments flying next to the CzP, generally with the highest mass to effective transverse surface ratio, left traces of their conical FU on the CzP overpressure records, which allowed the determination of average velocities for some of them across the access path to the CzP, whereas these velocities ranged from approx. 1700 m/s at a distance of approx. 8 m and (1500 m/s to 1600 m/s) at a distance of 16 m to approx. 1300 to 1400 m/s at a distance of 26 m from the epicentre. Average access velocities of the selected fragments to the field marks were determined on the basis of the video recording ranged from approx. 1800 m/s at a distance of 5 m to approx. 1500 m/s at a distance of 20 m from the explosion epicentre.